1997
DOI: 10.1002/(sici)1096-9861(19971215)389:2<348::aid-cne11>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Topographical distribution of neurons containing endothelin type A receptor in the rat brain

Abstract: Endothelin (ET) was originally identified as a vasoactive peptide biosynthesized in vascular endothelial cells. Because ET has also been found in the brain as a neuropeptide, it has been thought to belong to the group of brain-vascular peptide hormones. To date, type A and type B receptors for ET have been found. To elucidate the topographic distribution of type A receptor (ET-AR) in the brain, we raised a specific antibody to the C-terminal (64 amino acids) peptide of rat ET-AR and immunostained rat brain sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 27 publications
2
20
1
Order By: Relevance
“…Further experiments are under way in our laboratory, showing that these neurons are also endothelin type A receptor (ET-AR) immunopositive (data, not shown). Kurokawa et al [20] have already reported that the distribution of a major part of ET-AR-immunopositive neurons is quite similar to that of catecholamine neurons, which is in agreement with our above observations. The previous reports suggest that the neurons from RVLM to intermediolateral gray column (IML) are either glutamate or adrenaline-containing [10].…”
Section: Discussionsupporting
confidence: 93%
“…Further experiments are under way in our laboratory, showing that these neurons are also endothelin type A receptor (ET-AR) immunopositive (data, not shown). Kurokawa et al [20] have already reported that the distribution of a major part of ET-AR-immunopositive neurons is quite similar to that of catecholamine neurons, which is in agreement with our above observations. The previous reports suggest that the neurons from RVLM to intermediolateral gray column (IML) are either glutamate or adrenaline-containing [10].…”
Section: Discussionsupporting
confidence: 93%
“…These previous studies used radioimmunoassay to determine the presence of ET receptors. An apparently conflicting result was obtained by Kurokawa et al (1997) who, using antibodies to the amino terminus of ET A , observed the opposite in the rodent brain viz. abundant ET A immunolabelling.…”
Section: Discussionmentioning
confidence: 91%
“…ET-1 blood levels alter key regulatory mechanisms of the cerebral circulation by modulating endothelial NO synthase phosphorylation and NO production through Rho-associated protein kinase (Faraco et al, 2013). The significant vasoconstrictive and pro-inflammatory ET-1 effects at selected brain loci could also alter leptin regulatory circuits and BBB transport in urban children (Freeman et al, 2014;Faraco et al, 2013;Kurokawa et al, 1997;Mathison et al, 2007;Rossi and Maliszewska-Scislo, 2008). The ET1-induced cerebrovascular dysfunction may contribute to the vascular alterations associated with neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%